2017
DOI: 10.1007/s11274-016-2195-0
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activity of sub-inhibitory concentrations of curcumin with ceftazidime and ciprofloxacin against Pseudomonas aeruginosa quorum sensing related genes and virulence traits

Abstract: Quorum sensing (QS) system in Pseudomonas aeruginosa may be an important target for pharmacological intervention. The present study aimed to investigate the synergetic activity of sub-MIC concentrations of curcumin (C) with ceftazidime (CAZ) and ciprofloxacin (CIP) against P. aeroginusa QS system. We determined the MIC and synergistic activity of C, CAZ and CIP against P. aeroginusa PAO1 using broth microdilution and checkerboard titration methods. The activity of sub-MIC (1/4 and 1/16 MIC) concentrations of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 25 publications
2
34
1
Order By: Relevance
“…In a recent study, Otani et al (2018) showed that sub-MICs of ceftazidime reduce biofilm volume, inhibit twitching motility, and repress gene expression involved in bacterial adhesion and matrix production of P. aeruginosa PAO1. Roudashti et al (2017) had previously noticed this effect of cephalosporin on motility and biofilm formation for the same strain.…”
Section: Effectiveness Of Conventional Antibioticsmentioning
confidence: 56%
“…In a recent study, Otani et al (2018) showed that sub-MICs of ceftazidime reduce biofilm volume, inhibit twitching motility, and repress gene expression involved in bacterial adhesion and matrix production of P. aeruginosa PAO1. Roudashti et al (2017) had previously noticed this effect of cephalosporin on motility and biofilm formation for the same strain.…”
Section: Effectiveness Of Conventional Antibioticsmentioning
confidence: 56%
“…The use of subinhibitory concentrations of macrolides was recently reported as another option for developing novel treatment strategies for P. aeruginosa infections [19]. Indeed, it has been shown that QS inhibitors work synergistically with antibiotics [20][21][22]. Thus, the application of QS inhibitors with standard antibiotics could be a promising strategy to attenuate biofilm infections [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research in the past half century has demonstrated that beside its antioxidant, anti‐inflammatory, and anticancer action, curcumin also exerts antimicrobial effects (Aggarwal et al, ). In particular, it has bactericidal activity, it can synergize with antibiotics, and it also targets the virulence factors of several pathogens (Brown, ; Packiavathy, Sasikumar, Pandian, & Veera, ; Roudashti, Zeighami, Mirshahabi, Bahari, Soltani, & Haghi ; Tyagi, Singh, Kumari, Kumari, & Mukhopadhyay, ). Nontuberculous, rapidly growing mycobacteria (RGM) belonging to the Mycobacterium abscessus complex ( M. abscessus subsp.…”
Section: Introductionmentioning
confidence: 99%